Increase of Urinary 5-Hydroxyindoleacetic Acid Excretion but Not Serum Chromogranin a Following Over-The-Counter 5-Hydroxytryptophan Intake. (2008) - Joy, Tisha; Walsh, Grace; Tokmakejian, Sonya; Van Uum, Stan HM
Abstract : BACKGROUND: 5-hydroxyindoleacetic acid (5-HIAA) excretion is commonly measured for biochemical detection of carcinoid tumours. A 77-year-old woman was referred for elevated 24 h urine 5-HIAA excretion (510 μmol/day; normal is less than 45 μmol/day) and serum chromogranin A (CgA) (72.1 U/L; normal is less than 18 U/L), both subsequently normalized after discontinuation of 5-hydroxytryptophan (5-HTP). 5-HTP, a precursor of serotonin, is not commonly listed as a substance that increases 5-HIAA levels in urine. The effect of 5-HTP on CgA has not been previously described. OBJECTIVES: To determine whether, and to what extent, oral 5-HTP increases urine 5-HIAA excretion and serum CgA levels in healthy volunteers. PATIENTS AND METHODS: A randomized, prospective, double-blind, placebo-controlled crossover study, with a four-day washout period, was performed in a general community setting. Eight healthy subjects aged 22 to 58 years were recruited by advertising. Bedtime ingestion of 5-HTP 100 mg/day was compared with placebo ingestion for 10 days. Twenty-four hour urine excretion of 5-HIAA and serum CgA were the main outcome measures. RESULTS: Median (range) urinary 5-HIAA excretion was 204 μmol/day (22 μmol/day to 459 μmol/day) during 5-HTP intake, compared with 18 μmol/day (12 μmol/day to 36 μmol/day) during placebo intake (P=0.017). 5-HTP did not affect clinical symptoms or serum CgA levels. CONCLUSIONS: Oral 5-HTP increases urinary 5-HIAA excretion with considerable interindividual variation. In a small number of subjects, oral 5-HTP did not affect serum CgA levels. Therefore, increased 5-HIAA levels with normal CgA levels may suggest 5-HTP ingestion. The use of over-the-counter 5-HTP should be excluded as the cause of increased urinary 5-HIAA levels before initiating diagnostic tests to search for a carcinoid tumour. 5-HTP should be added to popular references as a substance that may cause increased 5-HIAA excretion.